2002
DOI: 10.1046/j.1365-3121.2002.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic methane layers: the hydrocarbon seep bubble deposition hypothesis

Abstract: Bubble plumes from hydrocarbon seeps drive upwelling flows in the water column that can disappear if the bubbles dissolve. This may lead to formation of a layer enriched in gases and substances transported by the bubbles, a process we term bubble deposition. A review of observed dissolved methane layers in the North Sea showed their existence in an area of active seeping pockmarks at a height of ∼ 20–30 m above the sea bed, well below the thermocline. To test the bubble deposition hypothesis, rising seep bubbl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 32 publications
1
44
0
2
Order By: Relevance
“…Deep-water seeps form large bubbles too [33]. Our result in Figure 5 implies that salinity stratification of the water column would not affect the rise velocity and gas exchange of seep bubbles rising from ocean depth.…”
Section: Salinity Effect On Large Bubble Sizesmentioning
confidence: 67%
“…Deep-water seeps form large bubbles too [33]. Our result in Figure 5 implies that salinity stratification of the water column would not affect the rise velocity and gas exchange of seep bubbles rising from ocean depth.…”
Section: Salinity Effect On Large Bubble Sizesmentioning
confidence: 67%
“…The rapidity of this process strongly depends on the bubble size, the rising velocity, as well as the composition and conditions of the surrounding medium and the presence of upwelling flows 59 . Several studies have demonstrated that methane escapes the 320 bubbles well before final bubble dissolution 11,56,60,61 .…”
Section: Discussionmentioning
confidence: 99%
“…Bubbles from seeps that are unable to saturate the plume water continue to lose CH 4 throughout the water column. Given enough time (sufficient depth), the bubbles may even dissolve completely (e.g., Leifer and Judd 2002).…”
Section: Discussionmentioning
confidence: 99%